Dynamics of B Cell Recovery In Kidney/Bone Marrow Transplant Recipients. Issue 11 (November 2017) - Gao, Baoshan; Gu, Yiming; Rong, Chunshu; Moore, Carolina; Porcheray, Fabrice; Wong, Waichi; Preffer, Frederic; Saidman, Susan L.; Fu, Yaowen; Cosimi, Benedict; Sachs, David H.; Kawai, Tatsuo; et al.
Abstract : Background: Previous studies identified B cell gene signatures and predominance of specific B cell subsets as a marker of operational tolerance after kidney transplantation. These findings suggested a role for B cells in the establishment or maintenance of tolerance. Here we analyzed B cell recovery in 4 subjects, 3 of whom achieved tolerance after combined kidney/bone marrow transplantation. Methods: Peripheral B cell subsets were examined longitudinally by flow cytometry. Immunoglobulin heavy chain repertoire analysis was performed using next-generation sequencing. Lastly, the patients' serum reactivity to HLA was assessed by Luminex. Results: B cell counts recovered approximately 1 year posttransplant except for 1 subject who experienced delayed reconstitution. This subject resumed immunosuppression for acute rejection at 10 months posttransplant and underwent preemptive retransplantation at 3 years for chronic rejection. B cell recovery was accompanied by a high frequency of CD20 + CD24 high CD38 high transitional B cells and a diversified clonal repertoire. However, all 4 subjects showed prevalence of CD20 + CD27+ memory B cells around 6 months posttransplant when B cell counts were still low and the clonal B cell repertoire very limited. The predominance of memory B cells was also associated with high levels of somatically mutated immunoglobulin heavy chain variable sequences and transient serum reactivity to HLA. Conclusions: Our observations reveal the presence of memory B cells early posttransplant that likely escaped the preparative regimen at a time consistent with the establishment of tolerance. Further studies are warranted to characterize the functional properties of these persisting memory cells and evaluate their potential contribution to tolerance induction. Abstract : In 3 tolerant renal transplant recipients after kidney and bone marrow transplantation, memory B cells were predominant early posttransplantation when tolerance was evolving. While transitional B cells increased only after immunosuppression withdrawal raising doubts regarding their roles during tolerance induction. Supplemental digital content is available in the text.